Teachers’ Reflection towards the Experiences of Teaching English On-Line During Pandemic and Off-Line In New Normal Era - Aida Fitrianah Zen (JETS: Journal of English Teaching Strategies, 2022)
Instructing amid the Covid-19 widespread is challenging for teachers who have never implemented online or virtual learning. There are many challenges occur according to the implementation of  remote teaching. It is necessary to comprehend the reflection of teachers‘ performance in online teaching as the contribution for school policy makers to develop teachers’ quality through enhancing technology-based learning. The purpose of this study was to investigate the reflections of teachers on online learning during the pandemic and learning in the new normal.  From the results of interviews with several teachers, it is indicated that students’ motivation, the role of parents, an unstable network, supporting devices, the ability to purchase data packages, and geographic location were all shown to be problems during online learning. Furthermore, throughout the pandemic, online learning has an impact on students' English learning achievement, particularly in listening and speaking skills. Teachers also expressed some reflections as a means of improving future learning, such as the need for collaborative efforts between teachers and guidance counselor in motivating and guiding students, the formation of study groups and teacher visits, and the improvement of technology-based learning skills by teachers.  It also found that the barriers of teaching in the new normal is students’ low selfdiscipline and the limited time allocation of learning. Moreover, off-line is more effective than online learning. Offline learning encourages students to comprehend learning context better and offers accessibility to the teachers for monitoring the students ‘ learning performance.